Analysis of Data Relevant to Establishing Outer Limits of a Continental Shelf under Law of the Sea Article 76 - Jakobsson, Martin; Mayer, Larry; Armstrong, Andrew (The International Hydrographic Review, 2003)
Coastal states may extend the limits of their juridically defined continental shelf beyond 200 nautical miles from their baselines under the provisions set forth in Article 76 of the United Nations Convention on the Law of the Sea (UNCLOS). In a preparatory desktop study, the University of New Hampshire’s Center for Coastal and Ocean Mapping/Joint Hydrographic Center analysed existing U.S. bathymetric and geophysical data holdings, identified data adequacy, and survey requirements to prepare a U.S. claim beyond the Exclusive Economical Zone (EEZ). In this paper we describe the methodology for our desktop study with particular emphasis on how we assembled and evaluated the existing data around the shelf areas of the United States, and estimated where additional surveys may be required.